2003
DOI: 10.1093/brain/awg114
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fibres and cultured muscle cells express the B7.1/2-related inducible co-stimulatory molecule, ICOSL: implications for the pathogenesis of inflammatory myopathies

Abstract: Inducible co-stimulator ligand (ICOSL), a member of the B7 family of co-stimulatory molecules related to B7.1/2, regulates CD4 as well as CD8 T-cell responses via interaction with its receptor ICOS on activated T cells. Here we examined the expression and the functional relevance of ICOSL in human muscle cells in vivo and in vitro. We investigated 25 muscle biopsy specimens from patients with polymyositis, dermatomyositis, inclusion body myositis, Duchenne muscular dystrophy and non-myopathic controls for ICOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 37 publications
4
72
0
6
Order By: Relevance
“…80 Its expression in muscles has been demonstrated under in vivo physiological and pathological conditions, as well as in in vitro cultured human myoblasts following TNF-a stimulation. 81 Notably, the presence of a neutralizing anti-ICOSL monoclonal antibody markedly reduced the production of Th1 and Th2 cytokines by activated allogenic CD4 + T cells, when cocultured with myoblasts expressing MHC II and ICOSL. The ICOS-ICOSL interactions can represent an important immunostimulatory pathway for T cell effector functions driving inflammation in muscles.…”
Section: Intrinsic Apc Capacities Of Myoblasts and Myocytesmentioning
confidence: 95%
See 1 more Smart Citation
“…80 Its expression in muscles has been demonstrated under in vivo physiological and pathological conditions, as well as in in vitro cultured human myoblasts following TNF-a stimulation. 81 Notably, the presence of a neutralizing anti-ICOSL monoclonal antibody markedly reduced the production of Th1 and Th2 cytokines by activated allogenic CD4 + T cells, when cocultured with myoblasts expressing MHC II and ICOSL. The ICOS-ICOSL interactions can represent an important immunostimulatory pathway for T cell effector functions driving inflammation in muscles.…”
Section: Intrinsic Apc Capacities Of Myoblasts and Myocytesmentioning
confidence: 95%
“…The ICOS-ICOSL interactions can represent an important immunostimulatory pathway for T cell effector functions driving inflammation in muscles. 81,82 Two other members of this family, the B7-homologue B7-H1 (programmed death ligand-1 PD-L1) and B7-H3, show negative costimulatory effects, pointing out the importance of these molecules in regulating T-cell tolerance and autoimmunity. 79 In specimens of inflammatory myopathies, B7-H1 has been localized on muscle fibres as well as on mononuclear cells, and it can be induced in cultured human myoblasts by IFN-g. 83 In coculture experiments, the presence of a neutralizing anti-B7-H1 antibody markedly enhances the production of IFN-g and IL-2 by pre-activated CD4 + and CD8 + T cells, and the expression of the T-cell activation markers CD25, ICOS, and CD69.…”
Section: Intrinsic Apc Capacities Of Myoblasts and Myocytesmentioning
confidence: 99%
“…Herein, we show that this may be due to, at least in part, inefficient effector cell activation as the result of lack of costimulation. Absence of costimulatory CD80 and CD86, previously described as a shared feature of TE671 embryonal RMS cells and normal muscle, 31 is shown to be a more general property of alveolar and embryonal RMS cell lines (n Z 5) and RMS in vivo (n Z 23). In addition, ICOS-L expression was found to be augmented by TNFa, which has potential relevance for vaccination strategies in patients with RMS.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, the induction of ICOS-L in a subset of RMS cell lines is of particular interest to improve therapeutic efficacy because ICOS-Lemediated costimulation is crucial for specific T cells to effectively lyse non-RMS tumor cells 7,8 and to destruct inflamed human skeletal muscle in vivo. 31 ajp.amjpathol.org -The American Journal of Pathology…”
Section: Adoptive T-cell Therapy Of Rmsmentioning
confidence: 99%
“…Early studies have previously revealed that the antigen‐presenting properties of human myocytes exceed the mere bearing of MHC class I molecules. In fact, muscle fibers can be categorized as facultative antigen‐presenting cells, that in a proinflammatory milieu can upregulate MHC class II molecules, express intercellular adhesion molecule (ICAM)‐1 and ICOS ligand (ICOS‐L) 108, 109, 110. In line with this, MHC class II expressing muscle fibers are found in IBM 108.…”
Section: Pathomechanisms In Ibmmentioning
confidence: 93%